2020
DOI: 10.1101/2020.06.24.20139436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of a novel, low-cost, scalable vaporized hydrogen peroxide system for sterilization of N95 respirators and other COVID-19 related personal protective equipment

Abstract: Due to the virulence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the pathogen responsible for the respiratory disease termed COVID-19, there has been a significant increase in demand for surgical masks and N95 respirators in medical clinics as well as within communities operating during the COVID-19 epidemic. Thus, community members, business owners, and even medical personnel have resorted to alternative methods for sterilizing face coverings and N95 respirators for reuse. While significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Overall, 16 studies measured disinfection and durability 12, 15, 19, 20, 22, 27-30, 33, 36, 47, 49, 51, 62, 64 , 16 studies measured only disinfection 13, 18, 23, 24, 31, 38, 40, 41, 43, 44, 48, 56, 63, 65-67 and 26 studies measured only durability 7, 14, 16, 17, 21, 25, 26, 32, 34, 35, 37, 39, 42, 45, 46, 50, 52-55, 57-61, 68 . Thus, 32 studies measured disinfection and 42 measured durability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, 16 studies measured disinfection and durability 12, 15, 19, 20, 22, 27-30, 33, 36, 47, 49, 51, 62, 64 , 16 studies measured only disinfection 13, 18, 23, 24, 31, 38, 40, 41, 43, 44, 48, 56, 63, 65-67 and 26 studies measured only durability 7, 14, 16, 17, 21, 25, 26, 32, 34, 35, 37, 39, 42, 45, 46, 50, 52-55, 57-61, 68 . Thus, 32 studies measured disinfection and 42 measured durability.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 92 individual mask disinfection tests were conducted across 32 studies 12, 13, 15, 18-20, 22-24, 27-31, 33, 36, 38, 40, 41, 43, 44, 47-49, 51, 56, 62-67 . The masks tested included: 75 tests with N95s (82%), 5 (5%) with cloth masks, 4 (4%) with surgical masks, three (3%) with KN95s, three (3%) with Tyvek, and 1 (1%) with a plastic face shield and 1 (1%) unspecified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the work to date has focused on sterilization of respirators for subsequent reuse. While a few studies have been completed and submitted to preprint servers after waiting for data from extant labs [24][25][26][27][28][29], a number of other preprints [30,31] and publications [32][33][34] have developed apparatuses to measure filtration efficiency as best they can independently. There is significant heterogeneity in these setups; some are built with assistance from labs which study aerosols, others with equipment found on hand.…”
Section: Introductionmentioning
confidence: 99%